Immunologic detection of Giardia duodenalis in a specific pathogen–free captive olive baboon (Papio cynocephalus anubis) colony. (November 2017) - Saleh, Meriam N.; Thomas, Jennifer E.; Heptinstall, Jack R.; Herbein, Joel F.; Wolf, Roman F.; Reichard, Mason V.; Zajac, Anne M.
Several commercial Giardia immunoassays were evaluated in baboons for sensitivity and specificity as well as ease of use in a large specific pathogen–free (SPF) colony. An additional objective was to identify the assemblage(s) of Giardia duodenalis present in this baboon colony. A direct immunofluorescent antibody test (IFAT) was used as the reference test. Tests evaluated were a patient-side rapid test for dogs and cats, a human rapid test, and a well-plate ELISA designed for use with humans. Test sensitivities and specificities were compared using the McNemar paired t -test and were further evaluated for agreement using an unweighted Cohen kappa statistic. When compared to the IFAT reference, both human tests were more sensitive than the veterinary test. Based on PCR and sequencing of the G. duodenalis small-subunit ribosomal RNA and glutamate dehydrogenase loci, assemblage AI was present in this baboon colony. We found that 10 of the 110 (9%) baboons in this SPF colony were infected with a zoonotic strain of G. duodenalis .